2012
DOI: 10.1029/2011ja017464
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the inner electron diffusion region in collisionless magnetic reconnection

Abstract: [1] The Sweet-Parker analysis of the inner electron diffusion region of collisionless magnetic reconnection is presented. The study includes charged particles motion near the X-line and an appropriate approximation of the off-diagonal term for the electron pressure tensor. The obtained scaling shows that the width of the inner electron diffusion region is equal to the electron inertial length, and that electrons are accelerated up to the electron Alfvén velocity in X-line direction. The estimated effective pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…(5) U ez . This expression is consistent with past theories of E y component produced by the non-gyrotropic effects near the X-point (E NG y ) (e.g., Kuznetsova et al, 1998;Hesse et al, 1999;Dorfman et al, 2008;Divin et al, 2012), in which they derived…”
Section: Spatial Dimension Of the Electron Diffusion Region In The Z supporting
confidence: 78%
See 1 more Smart Citation
“…(5) U ez . This expression is consistent with past theories of E y component produced by the non-gyrotropic effects near the X-point (E NG y ) (e.g., Kuznetsova et al, 1998;Hesse et al, 1999;Dorfman et al, 2008;Divin et al, 2012), in which they derived…”
Section: Spatial Dimension Of the Electron Diffusion Region In The Z supporting
confidence: 78%
“…Similar scalings were also seen in past kinetic simulations (Hesse et al, 1999;Ricci et al, 2002;Daughton et al, 2006;Karimabadi et al, 2007;Divin et al, 2012), where they indicated that the dimension of the electron diffusion region in the x direction is proportional to (m e /m i )…”
Section: Spatial Dimensions In the X Directionsupporting
confidence: 61%
“…It is important to note that Divin et al, 21 in a related analysis of a mass ratio 1836 PIC reconnection simulation, have found a ¼ 0:36 (their parameter k a). It is not clear whether the difference between this value and the cluster of values in Table I represents mass ratio dependence or not.…”
Section: Discussionmentioning
confidence: 97%
“…Numerical simulations showed that the X-line region can contain several scales corresponding to different intensities of the current density carried by various particle populations (see, e.g., Hesse et al, 2006;Karimabadi et al, 2007;Divin et al, 2010, and references therein). For example, accelerated electrons can carry strong current, which provides a decrease of the scale L z in the vicinity of the X-line (Divin et al, 2012). However, here we assume that population of accelerated electrons is sufficiently small in comparison with the thermal background population.…”
Section: Model Of Electron Acceleration In X-linementioning
confidence: 99%
“…Corresponding components of the electric field are E z ∼ −z, E x ∼ x (see, e.g., analytical model by Korovinskiy et al, 2008). The amplitude of the scalar potential ϕ is defined by the pressure balance and can reach ∼ B 2 0 /4πn 0 e ∼ 1-10 keV, where n 0 is the plasma density in the X-line (Divin et al, 2012).…”
Section: Model Of Electron Acceleration In X-linementioning
confidence: 99%